Thermal conductivity enhancement of carbon fiber/epoxy composites via constructing three-dimensionally aligned hybrid thermal conductive structures on fiber surfaces. (5th January 2023) - Hao, Mengyuan; Qian, Xin; Zhang, Yonggang; Yang, Jiaming; Li, Chunjie; Gong, Haoting; Wang, Xuefei; Wang, Piaopiao; Liu, Li; Huang, Yudong
Abstract: Owing to high graphitization degree, polyacrylonitrile (PAN)-based high modulus carbon fiber (HMCF) can not only be used as the general structural reinforcement for advanced composites, but also be applied to improve the thermal conductivities (TC) of polymer composites. However, the enhancement of through-thickness TC of composites remains extremely challenging due to fiber anisotropy and the lack of continuous thermal conductive path among CFs. In the present work, three-dimensional (3D) hybrid thermal conductive structures were constructed onto PAN-CF surfaces to prepare HMCF/epoxy composites with high through-thickness TC. In details, crosslinked high thermal conductive Ni/CNT hybrid network was firstly electrodeposited onto HMCF surfaces, which also provided abundant channels for the impregnation of easily graphitized poly-p-phenylene benzobisoxazole (PBO)/graphene oxide (GO). The freeze-drying assisted grafting of 3D-oriented PBO/GO and high-temperature heat treatments were further conducted to create the 3D graphite structures onto CFs. The interconnected Ni/CNT networks with 500 nm thickness and 3D aligned PBO-graphite bridging structures with an average thickness of 1 μm contributed to the formation of efficient heat conduction pathways along the through-thickness direction. Additionally, high-temperature treatment had been proven critical to effective heat conductions. Especially, PAN-CF with the 3D hybrid thermal conductive structures treated at 2100 °C (named CNC@PG-2100) exhibited superior TC, and the maximum TC value of CNC@PG-2100 reinforced composites reached 5.39 W/(m‧K) at the CF loading of 55%, which improved by 573% compared to that of composites reinforced by untreated PAN-CFs (0.94 W/(m‧K)). Graphical abstract: Image 1